University Open Data Policy in the Context of the Digital Transformation Strategy for Science and Higher Education - OlgaA. IVANOVA; Svetlana B. VERESHCHAK; Anton K. KUZNETSOV (Communications of International Proceedings, 2021)
One of the important directions of the digital transformation of universities – the implementation of the university open data policy, is analyzed in the article. The policy's goal in the field of the open data is creation of the open data ecosystem for integration into the Russian and international educational process (including by linking their open data with open data of other universities), obtaining a maximum effect from using of the data by interested parties, creating an information basis for the concept of "Open University". The formation and the development of the university's open data ecosystem includes a number of the stages: the development of an open data infrastructure, the formation, publication and updating of the university's open data sets, formation of an open data ecosystem and an open data culture. The main activities are revealing within each stage. This research is based on the interdisciplinary approach. An integrated approach is used to the problem of the formation and the implementation of the university's policy in the field of the open data. The authors make the conclusion that the formation of the open data ecosystem of a university creates unique opportunities for the effective and competitive promotion of university's educational programs, strategic projects, results of Scientific Research Work, products and services of a university, expansion of an intellectual, scientific, practical and technological potential of a university, integration into the global scientific and educational process of creating and using of younger generation`s data.
Keywords: Digitalization of Higher Education; Digital Educational Environment; Digitalisation; Digital University; Ecosystem; Open Data